Preliminary studies on the extraction of phenolic compounds from olive leaves of Portuguese cultivars - Cornamusaz, Rita (2018)
Poster presented at the 2nd International Congress of CiiEM: “Translational Research and Innovation in Human in health Sciences”. Egas Moniz, Caparica, 11-13 June 2017